A Case report on remarkable healing by secondary intention in a hemi-maxillectomy patient rehabilitated with obturator prosthesis - Reddy, Chaitanya; P, Sesha Reddy; Pampana, Sravani; Guduri, Vineeth (International Journal of Dental Materials, 2024)
This case report describes a situation in which an impressive recovery through secondary intention occurred in a patient who had a hemi-maxillectomy, and this was followed by comprehensive rehabilitation involving multiple disciplines. The pre-surgical prosthetic planning was done before the surgical excision of the tumour. Phased treatment was executed with a surgical obturator immediately post resection, hollow-bulb interim obturator during the healing phase and cast partial denture definitive obturator after recovery. Rapid healing was achieved by secondary intention, and a drastic reduction in the volume of defects was observed. Follow-up revealed successful patient rehabilitation to lead a good quality of life.